DYSTOPIA IN KHALID TAWFIK UTOPIA - Nazemian, Houman (PEOPLE: International Journal of Social Sciences, 2019)
Unlike Utopia, dystopia represents a city full of poverty, frustration and misery in fiction; it is a new phenomenon motivated by human failures and various historical disasters, such as World Wars, the Cold War, the nuclear war, which have led famous writers, like Aldous Huxley and George Orwell, to depict devastation in their novels instead of portraying utopian contexts in the twentieth century. Dystopia has emerged recently in Arabic literature, especially after the events of the Arab Spring, and the complication of various social and political problems in some Arab countries. Ahmed Khalid Tawfik, a contemporary Egyptian writer, was one of the most prominent contemporary writers in the horror genre and, generally, fiction. His Utopian novel, in contrast to his title, depicts a dystopia. The present study was conducted in order to examine, relying on social criticism, especially the views of Lucien Goldmann, the dichotomy of the image of self and others in contemporary Arabic novel and the worldview reflected in this novel.